Maternal employment experiences, attention problems and behavioral performance : a mediational model - Barling, Julian [Verfasser]; MacEwen, Karyl E. [Verfasser] (My University, 1991)
"The present study posits and empirically tests a process model examining the effects of interrole conflict, satisfaction with, and commitment to the role of employed mother on a self-report measure of cognitive difficulties and a behavioral measure relevant to work performance (proof reading)- Fifty-three full-time employed mothers with at least one child living at home participated. The proposed model, tested using Lisrel VI, provided an excellent fit to the data. Specifically, interrole conflict exerted an indirect effect on proof reading performance, mediated by self-reported attention and concentration difficulties. Satisfaction with an commitment to the role of employed mother were not related to either proof reading performance or self-reported cognitive difficulties." (author's abstract) ((en)) In dem Beitrag werden die Rollenprobleme von erwerbstätigen Müttern behandelt. Am Beispiel einer Tätigkeit von Sekretärinnen (dem Korrekturlesen) wird untersucht, welchen Einfluss Rollenkonflikte, Zufriedenheit mit und Engagement in der Mutterrolle auf die Aufgabenerledigung im Beruf haben. (IAB)
Beschäftigungserfahrungen von Müttern, Probleme der Aufmerksamkeit und Verhalten - Ein Vermittlungsmodell
Keywords: P 1.3 Frauen; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 2.4.2 Lebenskonzepte, -stile, Werte; S 6.4.3.5 Bürofach-, Bürohilfskräfte; G 2.3.1 Arbeitsteilung & -organisation; G 2.4.3 Privater & Familiärer Wandel; G 2.3.3 Arbeitsformen, Techniken; Mütter; Frauenerwerbstätigkeit; Doppelrolle; Rolle; Konflikt; Zufriedenheit; Sekretärin; Frauen in Einzelberufen; Frauenarbeit; Berufsproblem; Arbeitsleistung; Beruf und Familie; Quantitative Angaben